Fish oil supplementation of rats fed a high fat diet during pregnancy improves offspring insulin sensitivity - Satokar, Vidit V.; Vickers, Mark H.; Reynolds, Clare M.; Ponnampalam, Anna P.; Firth, Elwyn C.; Garg, Manohar L.; Barrett, Carolyn J.; Cutfield, Wayne S.; Albert, Benjamin B. (Frontiers in Nutrition, 2022)
Introduction In rats, a maternal high-fat diet (HFD) leads to adverse metabolic changes in the adult offspring, similar to the children of mothers with obesity during pregnancy. Supplementation with a high dose of fish oil (FO) to pregnant rats fed a HFD has been shown to prevent the development of insulin resistance in adult offspring. However, the effects of supplementation at a translationally relevant dose remain unknown. Aim To determine whether supplementation with a human-relevant dose of FO to pregnant rats can prevent the long-term adverse metabolic and cardiovascular effects of a maternal HFD on adult offspring. Methods Female rats (N=100, 90 days of age) were assigned to HFD (45% kcal from fat) or control diet (CD) for 14 days prior to mating and throughout pregnancy and lactation. Following mating, dams received a gel containing 0.05ml of FO (human equivalent 2-3ml) or a control gel on each day of pregnancy. This produced 4 groups, CD with control gel, CD with FO gel, HFD with control gel and HFD with FO gel. Plasma and tissue samples were collected at day 20 of pregnancy and postnatal day 2, 21 and 100. Adult offspring were assessed for insulin sensitivity, blood pressure, DXA scan, and 2D echocardiography. Results There was an interaction between maternal diet and FO supplementation on insulin sensitivity (p=0.005) and cardiac function (p<0.01). A maternal HFD resulted in impaired insulin sensitivity in the adult offspring (p=0.005 males, p=0.001 females). FO supplementation in the context of a maternal HFD prevented the reduction in insulin sensitivity in offspring (p=0.05 males, p=0.0001 females). However, in dams consuming CD, FO supplementation led to impaired insulin sensitivity (p=0.02 males, p=0.001 females), greater body weight and reduced cardiac ejection fraction. Conclusions The effects of a human-relevant dose of maternal FO on offspring outcomes were dependent on the maternal diet, so that FO was beneficial to the offspring if the mother consumed a HFD, but deleterious if the mother consumed a control diet. This study suggests that supplementation with FO should be targeted to women expected to have abnormalities of metabolism such as those with overweight and obesity.